NETWORKING ANALYSIS, ADOPTION OF ACCOUNTING INFORMATION TECHNOLOGY, DYNAMIC CAPABILITIES ON ORGANIZATIONAL PERFORMANCE WITH CORPORATE STRATEGY AS MODERATING VARIABLES - Bayu Seno Pitoyo; Tri Widyastuti; Nurmala Ahmar; Apollo Daito; Harnovinsah Harnovinsah (International Journal of Social Science, 2023)
Small and medium industry (IKM) is a business that produces various types of products needed by various types of living things such as humans, animals and plants. The purpose of this study was conducted to develop variables that Networking Analysis, Adoption of Accounting Information Technology, Dynamic Capabilities on Organizational Performance with Corporate Strategy as Moderating Variables. The research method uses the quantitative to determine the relationships and influences between variables, with 205 respondents. Selection of the sample using hair method and data collection using a questionnaire. Data is processed using Structural Equation Modeling (SEM) using SMART-PLS. The results showed that the networking, information technology adoption, dynamic capabilities and business strategy affect the performance of SMEs. The moderating role of business strategy is able to strengthen the effect of networking and dynamic capabilities on IKM performance, but weakens the influence of adoption of accounting information technology on IKM performance